Total Quality Management and the Role of Management Accountants on Organisational Performance: The Service Sector in Malaysia - Ghassan, Gheyath; Maelah, Ruhanita; Mohd Amir, Amizawati; Farhan, Mohammed Fadhil (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper Research aims: This study examines the relationship between total quality management (TQM), the role of the management accountant and organisational performance among the service sector in Malaysia. Design/Methodology/Approach: This study collects data from 100 private service organisations in Malaysia via a self-administered printed questionnaire. Data collected are analysed using partial least squares (PLS) 3.0. Research findings: The results reveal that TQM has a positive significant impact on organisational performance. The TQM’s practice of focussing more on customers and the designing of services also show significant effects on organisational performance. This study finds that management accountants do not moderate the relationship between TQM and organisational performance. Theoretical contribution/Originality: This study expands the previous literature by examining the role of the management accountant as a moderator between TQM and organisational performance. Practitioner/Policy implications: The results derived from this study can be used to facilitate the application of TQM in service organisations so as to enhance their organisational performance. The findings can also assist managers in the service organisations to determine the functions of their management accountants because this can impact on the successful adoption of TQM. Research limitation/Implications: The limitations of this study includes its scope which is confined to only the service industry. Future research should expand further to cover other industries. Keywords: TQM, Organisational Performance, Role of the Management Accountant, Service JEL Classification: M41